Complex Prophylaxis and Prognosis of Inflammatory Complications after Dental Implantation - Mustafaev, Magomet Sh. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim and Scope: The main task of dental implantation at the modern stage of its development remains the struggle against complications. At present, there is no generally accepted set of biomarkers and an algorithm for their use for early diagnosis of the risk of complications and monitoring of osseointegration. The objective of the study is to increase the effectiveness of dental implantation by developing a method of complex prophylaxis and prediction of development of complications in the long-term perspective after the operation. Materials and Methods: A method of preventing the development of complications of dental implantation by applying a complex of antioxidant vitamins and amino acids was approved and introduced. Results and Discussion: The significance of serum and local indices of the cytokine profile as diagnostic and prognostic parameters in patients with peri-implantitis developed afterthe operative intervention, was determined. It was found that patients with simultaneous installation of 5 or more implants, in spite of competent surgical work, are at higher risk of complications development in the long-term due to the presence of peculiarities of the mediator reaction with the prevalence of local inflammation processes. Conclusion: Perhaps a promising direction of prevention in the future will be the development of methods for targeted delivery of antioxidant substances to tissues to fill the deficit of protective components and establish an equilibrium.